Perception of medical professionalism in students of the last year of their career in a Peruvian university. - Ticse, Ray (2021)
Objective: To describe concepts, experiences, and perspectives from senior (7th Year) medical students of a Peruvian university, regarding Medical Professionalism.  Material and Methods: A survey was applied to medical students that completed their Internship at the Faculty of Medicine of the Universidad Peruana Cayetano Heredia, during Results: The percentage of responses reached a 90.5%. The three most common responses were ethics (51.2%), a good doctor-patient relationship (43%), and knowledge (41.9%). Approximately eighty-one percent (81.4%) of the students “agreed” or “strongly agreed” with the fact that professionalism can be learned and taught. The contact with positive models from the faculty (4.26 / 5.00) was considered as the most useful method for learning about professionalism, while only 25.6% considered adequate the number of activities dedicated to the teaching of the topic. Conclusions: Medical interns consider ethics, good patient-physician communication, knowledge, respect and responsibility as the main attributes of medical professionalism. They perceived that their concept of professionalism was more influenced by positive faculty models than by formal academic activities.